STUDENT LEADERSHIP IN SCHOOL: INTERNALIZATION OF ENTREPRENEURIAL COMPETENCE AND CHARACTER - Lelahester Rina (Jurnal Manajemen dan Kewirausahaan, 2019)
This paper aims to find the effort of internalizing competence and entrepreneurial character of student in Satya Wacana Christian Elementary School and Juniour High School. The method used is a qualitative study through interview, observation and documentation, using data analysis from Spradley by analyzing of domain and its semanctical relation. The results showed that the internalization of entrepreneurial competence and character had been applied through leadership activities so as to form the character and leadership skills of students. This study has implications for the school's efforts to give full attention for students to play a role in leadership activities and to provide support through a curriculum that supports the internalization of entrepreneurial competence and character. Keywords: Entrepreneurial competence, Entrepreneurial character, Entrepreneurship education, Student leadership, Elementary levels.